(untitled) (Al-Qamar, 2020)
The purpose of this research is to show what distinguishes the Qur’ānic context in depicting the meanings of security and its issues and its transcendence, and to surround all its diversity in a comprehensive and inclusive way to advance the concepts of Qur’ānic discourse and reach the goal in the media about its goals and purposes, by revealing the peculiarities of the Qur’ānic expression in choosing letters and words and selecting its strongest in expressing meanings, this is called "reaching of meaning", and the accuracy in the use of words and the keenness of their expression in expressing intents and not others. The Qur’ānic style was characterized by the ease of words, their ease, the purity of their luster, and the lightness of their performance, while observing those subtle differences in the significance and the difference between the word and the other in expressing the meaning. The Noble Quran has chosen the most accurate expression, and one of the tunes, and put each word in its proper place in the systems with great skill and miracle rhetoric.